Energy Recovery from Split-Type Air Conditioners: Experimental Analysis of Integrated Water Heating Systems with Different Refrigerants - Haolia Rahman; Paulus Sukusno; Ainun Nidhar (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2025)
Air conditioning (AC) systems use the evaporator to absorb heat from the indoor air to provide cooling. By utilizing the condenser side, these systems can also operate as heat pumps for water heating. However, such applications remain limited in Indonesia. This study experimentally investigates a modified split-type AC unit retrofitted with a 40 L insulated hot-water tank and a 10 m long, 5/8